Tingkat Efisiensi Pengelolaan Zakat dengan Metode DEA pada BAZNAS Jawa Barat - Elviera Maharani; Mochamad Edman Syarief; Dadang Hermawan (Journal of Applied Islamic Economics and Finance, 2022)
This study aims to analyze the efficiency level of zakat management using the Data Envelopment Analysis (DEA) method at BAZNAS West Java for the 2015-2019 period. The sample in this study is the annual financial report of BAZNAS West Java. This type of research is descriptive quantitative research. There are several variables used in this study, the input variables consist of: (I1) Total Assets, (I2) Operational Costs, and the output variables consist of: (O1) Distribution of Zakat Funds, (O2) Revenue of Zakat Funds. The results of the study using the DEA method with the Constant Return to Scale (CRS) model showed that BAZNAS West Java was able to achieve the efficient category with an optimal scale in zakat management with a score of 1 or 100% in 2015-2019 and achieved a relatively maximum value and the actual value according to DEA calculation targets.